2017
DOI: 10.1038/srep45925
|View full text |Cite
|
Sign up to set email alerts
|

Chiral nanoparticles in singular light fields

Abstract: The studying of how twisted light interacts with chiral matter on the nanoscale is paramount for tackling the challenging task of optomechanical separation of nanoparticle enantiomers, whose solution can revolutionize the entire pharmaceutical industry. Here we calculate optical forces and torques exerted on chiral nanoparticles by Laguerre–Gaussian beams carrying a topological charge. We show that regardless of the beam polarization, the nanoparticles are exposed to both chiral and achiral forces with nonzero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…[249][250][251][252][253] There is no doubt that new developments in structured light beams will continuously boost the fields of optical manipulation. 254 Moreover, among the diverse optical trapping schemes discussed in this review, in our view, several topics have great potential to find exciting future applications, such as the optical trapping of metal particles [183][184][185][186][187][188][189] and chiral particles, 52,53 vacuum levitation, structured light in waveguides, [255][256][257][258][259] optical binding and other collective motions in structured light fields, 113,185,[260][261][262] quantum optomechanics, 30 and optical trapping for multidisciplinary applications. 32 In the future, besides SLMs and DMDs, more flexible, efficient and much less expensive devices will be developed to produce structured beams, which can help build the next generation of optical trapping technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[249][250][251][252][253] There is no doubt that new developments in structured light beams will continuously boost the fields of optical manipulation. 254 Moreover, among the diverse optical trapping schemes discussed in this review, in our view, several topics have great potential to find exciting future applications, such as the optical trapping of metal particles [183][184][185][186][187][188][189] and chiral particles, 52,53 vacuum levitation, structured light in waveguides, [255][256][257][258][259] optical binding and other collective motions in structured light fields, 113,185,[260][261][262] quantum optomechanics, 30 and optical trapping for multidisciplinary applications. 32 In the future, besides SLMs and DMDs, more flexible, efficient and much less expensive devices will be developed to produce structured beams, which can help build the next generation of optical trapping technology.…”
Section: Discussionmentioning
confidence: 99%
“…40 Crucially, in recent time, it was demonstrated that SAM can also be used for the selective 3D trapping of chiral micro-and nanoparticles. 52,53 It was shown that under appropriate conditions, a light beam with SAM can induce nonrestoring or restoring forces on chiral microparticles. 52 Similar results have been also reported on the interaction of chiral nanoparticles with chiral optical fields.…”
Section: Optical Torques For Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, this work opens the way for further experimental implementation by considering particles with smaller sizes, toward the grail of all-optical resolution of chiral entities at the nanoscale. Finally, we note recent theoretical discussions on the possible use of a chiral light field endowed with chiral features that are not associated with the polarization state, as is the case for light fields carrying optical-phase singularities [44], which is another option through which to explore the experimental feasibility of alternative chiral optomechanics approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods cannot make an effective discrimination between D- and L- enantiomers. On the other hand, various analytical techniques, including high-performance liquid chromatography (HPLC), thin-layer chromatography (TLC), capillary electrophoresis (CE), gas chromatography, mass spectrometry 25 36 , circular dichroism (CD) 37 , fluorometry 38 , nuclear magnetic resonance (NMR) protocols 39 , 40 and using chiral light fields 41 44 have been reported to distinguish the chirality of PA, Cys, and other chiral compounds. However, most of these techniques have several drawbacks such as laborious setup process, expensive chiral columns, complicated sample pretreatment, complex operation process and high-cost chiral stationary phases or chiral selectors.…”
Section: Introductionmentioning
confidence: 99%